2017
DOI: 10.3906/vet-1512-67
|View full text |Cite
|
Sign up to set email alerts
|

The cSNP scanning and expression analysis of the duck FTH1 gene

Abstract: Materials and methods Ethics statementAll procedures involving the care and use of animals conformed to US National Institutes of Health guidelines Abstract: Ferritin, heavy polypeptide 1 (FTH1) is a kind of ferritin complex that catalyzes the conversion of Fe(II) into Fe(III) to protect the cell from oxidative damage. Recent research has shown that FTH1 is also associated with several disease-related processes, such as inflammation and tumor progression and so on. In this study, the coding sequence (CDS) of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…FTH1 (Ferritin heavy chain 1) is the main subunit of ferritin, responsible for the oxidation and integration of ferrous ions to maintain the balance of ferrous ions in the body [ 46 ]. Some studies have shown that FTH1 is related to the egg-laying traits of chickens [ 47 ], and some studies have also proven that expression of FTH1 changed significantly after poultry were infected with some pathogenic bacteria and viruses [ 23 , 48 ]. After the interference of FTH1 , the five cytokines: IL-1B , IL-2 , IL-6 , TLR4 and MYD88 were all significantly down-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…FTH1 (Ferritin heavy chain 1) is the main subunit of ferritin, responsible for the oxidation and integration of ferrous ions to maintain the balance of ferrous ions in the body [ 46 ]. Some studies have shown that FTH1 is related to the egg-laying traits of chickens [ 47 ], and some studies have also proven that expression of FTH1 changed significantly after poultry were infected with some pathogenic bacteria and viruses [ 23 , 48 ]. After the interference of FTH1 , the five cytokines: IL-1B , IL-2 , IL-6 , TLR4 and MYD88 were all significantly down-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…These distinct results suggest that chickens may have different defense mechanisms against bacterial and viral infections. Zhang et al [28] found that the expression of FTH1 in liver and spleen of Jingding duck was significantly down-regulated after infection with duck hepatitis virus 1, and the expression of antiviral marker gene MX1 was significantly up-regulated in DF-1 cells transfected with the FTH1 plasmid. Sun et al [29] showed that after FTH1 silencing, the intracellular viability of Brucella decreased, and the apoptotic rate of macrophages increased.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al (2021b) proposed that circSnx12 is involved in ferroptosis during HF by targeting the miR-224-5p/ferritin heavy chain 1 (FTH1) axis. FTH1 is a ferritin complex that catalyzes the conversion of Fe 2+ into Fe 3+ to protect the cell from oxidative damage (Zhang et al, 2017). CircSnx12 acts as a sponge for miR-224-5p, and FTH1 is a target gene of miR-224-5p.…”
Section: A Circrna That Upregulates Ferritin Heavy Chainmentioning
confidence: 99%
“…HF is a complex syndrome with a high mortality rate (Zhang et al, 2017). The prognosis of patients with HF is generally poor (Zhang et al, 2017).…”
Section: Heart Failurementioning
confidence: 99%
See 1 more Smart Citation